Análisis de una metodología de restauración de ecosistemas en las áreas de conservación y usos sustentable del noroccidente Manabí - Cevallos Mendoza, Marcos Froilán (2025)
The objective of the research was to evaluate the efficiency of a monitoring methodology for restored areas in the Conservation and Sustainable Use Areas of northwestern Manabí. To do so, indicators were established for the monitoring methodology, the current state of the restored areas was diagnosed, and the value of the methodology used was analyzed. The methodology included a bibliometric analysis for the selection of relevant indicators, working groups with experts to define monitoring criteria, and field information gathering. Structured observations, growth and health measurements of vegetation, as well as data analysis using statistical tools were carried out. The results showed that monitoring is a key factor in ecological restoration, allowing the survival rate, species diversity, and ecosystem recovery to be evaluated. Deficiencies were identified in some restoration processes due to the lack of adequate funding and monitoring, which affects the sustainability of the projects. In conclusion, it was determined that the implementation of structured monitoring methodologies improves the effectiveness of restoration processes by providing reliable information for decision-making. It is recommended to strengthen the continuous monitoring of restored areas, ensure sustainable sources of financing and optimize the efficiency of the strategies used, since ecological restoration, accompanied by adequate management, guarantees the recovery of ecosystems and the conservation of biodiversity in the region.